Studies in the Grammar and Lexicon of Neo-Aramaic - Khan, Geoffrey 1958-; Noorlander, Paul (Open Book Publishers, 2021)
"The Neo-Aramaic dialects are modern vernacular forms of Aramaic, which has a documented history in the Middle East of over 3,000 years. Due to upheavals in the Middle East over the last one hundred years, thousands of speakers of Neo-Aramaic dialects have been forced to migrate from their homes or have perished in massacres. As a result, the dialects are now highly endangered. The dialects exhibit a remarkable diversity of structures. Moreover, the considerable depth of attestation of Aramaic from earlier periods provides evidence for pathways of change. For these reasons the research of Neo-Aramaic is of importance for more general fields of linguistics, in particular language typology and historical linguistics. The papers in this volume represent the full range of research that is currently being carried out on Neo-Aramaic dialects. They advance the field in numerous ways. In order to allow linguists who are not specialists in Neo-Aramaic to benefit from the papers, the examples are fully glossed."
Keywords: Middle East